How the teaching of indigenous languages among disparate multicultural groups in a South African corporate setting affect cohesion - Bauer, Nickolaus (Graduate School of Business (GSB), 2022)
This study is an attempt to develop further theoretical insights into the link between language and cohesion across class and race within organizations operating in contemporary South Africa. Due to the combination of extensive diversity and pernicious inequality inherited from the country's colonial history, English – and to a lesser extent, Afrikaans – enjoys disproportionate power in education, commerce and industry over the other languages across South Africa. Notwithstanding the constitutional imperative of linguistic equality, English is the dominant tongue of power, which has led to indigenous languages – African indigenous languages in particular – assuming a subservient position within society. This has led to a myriad of knock-on effects that have either reinforced existing complex societal problems or have birthed entirely new issues, all of which have stifled attempts to build a non-racial, equal and prosperous South Africa for all. By using the existing literature compiled on subjects such as linguistic diversity, language acquisition, multiculturalism, organisational cohesion and their interconnectedness, this study aims to discover new thinking on how language can be used as a tool to re-order hierarchies and diminish divisions within an organization primarily and society more broadly. By measuring the level of cohesion and language capability and drawing inferences to their respective impacts on each other, it was investigated whether solidarity can be built across racial and class lines. The initial research question the researcher sought to answer morphed slightly from a specific focus on how teaching of indigenous languages by blue-collar workers to executives could affect cohesion within an organization into how such languages classes could impact interorganizational cohesion when conducted by juniors for their seniors within any company. This not only resulted in the research becoming more industry-agnostic, but empowered my findings to become broader, conclusions more comprehensive and recommendations more extensive. Research groups were formed across a variety of organizations from different sectors and research was conducted over a period of eight months. The extensive data collection was at once longitudinal - as cohesion and linguistic capability were measured before, during and after the study through questionnaires and written tests – but also auto-ethnographic in the personal conclusions the researcher drew throughout the study based on his adult life as a purveyor of multilingualism and ardent supporter of multiculturalism. Although the results of the research showed little direct change in measurable cohesion among participants, the process of language learning conducted by juniors for seniors presented a meaningful strategy to not only forge unity among participants but also understanding among individuals from disparate backgrounds, with a specific focus on identity, culture and class. It prompts further study into how language can be an easily accessible tool to build consensus not only within organisations, but in South African society at large, which remains one of the world's most unequal.